Circular RNAs in intracranial aneurysms: Emerging roles in pathogenesis, diagnosis and therapeutic intervention - Ilgiz Gareev; Alina Shumadalova; Tatiana Ilyasova; Aferin Beilerli; Huaizhang Shi (Non-coding RNA Research, 2024)
Intracranial aneurysms (IAs) present a substantial health threat, given the potential for catastrophic ruptures and subarachnoid hemorrhages (SAH). Swift and effective measures for diagnosis and treatment are paramount to enhance patient outcomes and alleviate the associated healthcare burden. In this context, circular RNAs (circRNAs) have emerged as an intriguing area of investigation, offering promise as both diagnostic biomarkers and therapeutic targets for IAs. CircRNAs have demonstrated their influence on critical molecular and cellular processes underpinning IAs pathogenesis, revealing their pivotal role in understanding this complex ailment. Beyond their diagnostic potential, circRNAs hold great potential as prognostic markers, providing crucial insights into IAs rupture risk. The unique circular structure and their regulatory functions make circRNAs an enticing avenue for innovative therapeutic approaches. The ongoing study of circRNAs in the context of IAs is an exciting and rapidly evolving field that has the potential to revolutionize approaches to diagnosis, treatment, and prevention of this life-threatening condition. As research continues to unravel the intricate roles of circRNAs, they are poised to become invaluable tools in clinical practice, enhancing patient care and ultimately reducing the impact of cerebral aneurysms on both individuals and healthcare systems. This comprehensive review delves deeply into the world of circRNAs in the realm of IAs, elucidating their multifaceted roles in the onset and progression of this condition. Moreover, this review ventures into the diagnosis and therapeutic potential of circRNAs, exploring their possible applications in gene therapy and as targets for novel treatment modalities.